Serum high-mobility group box 1 protein level correlates with the lowest SaO2 in patients with sleep apnea: a preliminary study - Hyun Jin Min; Joon Soon Park; Kyung Soo Kim; Miran Kang; Ju Hee Seo; Joo-Heon Yoon; Chang-Hoon Kim; Hyung-Ju Cho (Brazilian Journal of Otorhinolaryngology, 2022)
Introduction: Serum level of high-mobility group box 1 protein is reportedly correlated with the severity of obstructive sleep apnea. Objective: We tried to evaluate the possibility of using the serum high-mobility group box 1 protein level as a biologic marker in obstructive sleep apnea patients. Methods: We generated a chronic intermittent hypoxia murine model that reflected human obstructive sleep apnea. Obstructive sleep apnea patients who underwent polysomnography were prospectively enrolled. Serum samples were obtained from mice and obstructive sleep apnea patients, and the serum high-mobility group box1 protein level was measured by enzyme-linked immunosorbent assay. Results: Serum high-mobility group box 1 protein level was 56.16 ± 30.33 ng/mL in chronic intermittent hypoxia and 18.63 ± 6.20 ng/mL in control mice (p < 0.05). The mean apnea-hypopnea index and respiratory disturbance index values of enrolled obstructive sleep apnea patients were 50.35 ± 27.96 and 51.56 ± 28.53, respectively, and the mean serum high-mobility group box 1 protein level was 30.13 ± 19.97 ng/mL. The apnea–hypopnea index and respiratory disturbance index were not significantly correlated with the serum high-mobility group box 1 protein level (p > 0.05). Instead, this protein level was significantly correlated with lowest arterial oxygen concentration (SaO2) (p < 0.05). Conclusion: High-mobility group box 1 protein may be involved in the pathogenesis of obstructive sleep apnea, and the possibility of this protein being a useful biologic marker in obstructive sleep apnea should be further evaluated.